- #1

Darkmisc

- 204

- 27

- Homework Statement
- (a+b)x + cy = bc

(b+c)y + ax = -ab

- Relevant Equations
- x - y = a + c

Answer:

x = c

y = -a

Hi everyone

Could someone please help with the above equation?

Here is the working for my attempt

ax + bx + cy = bc

by + cy + ax = -ab

ax + bx + cy = bc

by + cy + ax = -ab

b(x-y) = b(a + c)

x - y = a + c

a^2 + ac + ay + ab + bc + by + cy = bc

a+2 + ac + ay + by + by = -ab

b(a+c) = bc + ab

0 = 0

Is it correct to conclude from this that bc = -ab, and that c = -a?

If so, can I substitute that into

y (a + b + c) = -ab

to get y = -a?

The correct answer is x=c and y =-a, which fits into the above equations

Thanks

Could someone please help with the above equation?

Here is the working for my attempt

ax + bx + cy = bc

by + cy + ax = -ab

ax + bx + cy = bc

by + cy + ax = -ab

b(x-y) = b(a + c)

x - y = a + c

a^2 + ac + ay + ab + bc + by + cy = bc

a+2 + ac + ay + by + by = -ab

b(a+c) = bc + ab

0 = 0

Is it correct to conclude from this that bc = -ab, and that c = -a?

If so, can I substitute that into

y (a + b + c) = -ab

to get y = -a?

The correct answer is x=c and y =-a, which fits into the above equations

Thanks